Integrating multimorbidity education into undergraduate medical curriculum: A systematic review - Andrea Cuschieri; Bridget L. Ryan; Sarah Cuschieri (Future Healthcare Journal)
Multimorbidity is becoming highly prevalent across the globe. Current medical curricula predominantly focus on single-disease management, leaving future physicians underprepared to provide patient-centred care to address the multimorbidity epidemic. Through a systematic review, this short communication identified the current state of multimorbidity education in medical curricula and evaluated existing educational approaches. A narrative systematic review (CRD42024585500) of studies meeting stringent inclusion criteria focusing on multimorbidity education was conducted. The review found limited evidence regarding the integration and effectiveness of current educational approaches. Although multimorbidity education was associated with improved self-reported student confidence, there was a notable absence of structured, formal teaching frameworks, with education primarily occurring through informal clinical exposure. This systematic review discovered the absence of an evidence base on structured, validated teaching methods that are urgently needed to better prepare future physicians to manage patients with multimorbidity effectively.